Design of Virtual Network Mapping Algorithm Based on K-Best Perfect Matchings of Bipartite Graph - Jianjun Yu; Chunming Wu (Dianxin kexue)
To improve the feasibility of virtual node mapping，grounded on feasibility test theorem and node rank indicators used to measure node availability，the virtual network mapping iterative algorithm based on K-best perfect matchings of bipartite graph was proposed，aiming at reducing mapping cost.Experiment shows that the proposed algorithm increases virtual network construction request acceptance ratio and benefit cost ratio，and hence can improve profit of physical network service provider.